2020
DOI: 10.3389/fpsyg.2020.576120
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Sensory-Spatial Integration and Retrieval of Trained Motor Patterns for Body Coordination in Musicians and Dancers

Abstract: Dancers and musicians are experts in spatial and temporal processing, which allows them to coordinate movement with music. This high-level processing has been associated with structural and functional adaptation of the brain for high performance sensorimotor integration. For these integration processes, adaptation does not only take place in primary and secondary sensory and motor areas but also in tertiary brain areas, such as the lateral prefrontal cortex (lPFC) and the intraparietal sulcus (IPS), providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Integrated sensory information can describe the position, size, weight, shape, and displacement speed of objects, further optimizing action plans through continuous motor sensory feedback [ 55 ]. The simultaneous multi-sensory stimulation of the vestibule, muscles, joints, skin, and the visual, auditory, and olfactory senses forms multimodal information processing patterns and accelerates the formation of motor representations for better postural control [ 56 , 57 ]. Based on the principle of sensory integration, the MAST method aims for multi-sensory stimulation and increases constant interactions among the senses.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated sensory information can describe the position, size, weight, shape, and displacement speed of objects, further optimizing action plans through continuous motor sensory feedback [ 55 ]. The simultaneous multi-sensory stimulation of the vestibule, muscles, joints, skin, and the visual, auditory, and olfactory senses forms multimodal information processing patterns and accelerates the formation of motor representations for better postural control [ 56 , 57 ]. Based on the principle of sensory integration, the MAST method aims for multi-sensory stimulation and increases constant interactions among the senses.…”
Section: Discussionmentioning
confidence: 99%
“…No previous research has suggested that IPS0 is part of the motion-processing pathway. Instead, IPS0 is a highly multisensory area and frequently appears in studies of working memory (Bray et al 2015; Brigadoi et al 2017), motor planning (Buneo and Andersen 2006), spatial representation (Makin, Holmes, and Zohary 2007), and multimodal integration (Regenbogen et al 2018; Ladda, Wallwork, and Lotze 2020). Future work is needed to determine if the areas involvement is purely visual, or contains a representation of 3D space across multiple different modalities, such as 3D motion auditory cues.…”
Section: Discussionmentioning
confidence: 99%
“…Trimodal neurons in the ventral premotor cortex (PMv) were proposed [ 30 ], and Makin et al [ 33 ] proposed involved trimodal neurons in PMC and intra-parietal sulcus (IPS) where visual, tactile, and proprioceptive afferents are integrated within one neuron. More recently, experiments found further brain areas, such as the lateral prefrontal cortex (lPFC) and the intraparietal sulcus (IPS), that provide resources for specialized motor control in dance and music [ 59 ]. An additional spinal contribution to the modulation of the MEPs cannot be completely ruled out, because a modulated discharge rate of spindle afferents may be crucial when the muscle is progressively lengthened [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%